Avaliação da remoção de H2S de biogás por absorção química em soluções contendo íons de ferro preparadas eletroquimicamente - Mayer, Bruna (2019)
Biogas is the name given to the gas generated in the anaerobic digestion of organic matter. This consists mainly of CH4 and CO2, as well as traces of other components, such as H2S. Due to its high calorific value, it has been considered a potential source for alternative energy generation. However, for its energy use, it is necessary to remove H2S from biogas, as it is highly corrosive, damages human health and reduces the energy potential of the gas. There are several technologies for the removal of H2S from biogas. One of the technologies that has stood out is chemical absorption, which has the advantages of being able to work at ambient temperatures, selective removal of H2S and high efficiency. The objective of this research was to evaluate the removal of H2S from biogas by applying the principle of chemical absorption using solutions containing Fe ions. These solutions were produced electrochemically based on experimental designs that had as independent variables pH and electrolysis time and as a variable. response, the time to turn off solutions. The results indicated a good performance of H2S removal solutions when compared to distilled water. It was observed that the best results for the deactivation time can be found when higher pH values are used in the solutions, within the range applied in this study. Furthermore, it was possible to find a significant mathematical model that describes the solution deactivation time as a function of pH.